1982
DOI: 10.1677/joe.0.0950065
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin may play a role in the control of the human corpus luteum

Abstract: The effects of oxytocin on dispersed luteal cells from human corpora lutea of the menstrual cycle were studied. Oxytocin at a concentration of 4 mi.u./ml produced a slight increase in basal progesterone production. However, higher oxytocin concentrations (400 and 800 mi.u./ml) markedly inhibited both basal and human chorionic gonadotrophin-induced progesterone production. These data provide evidence for an effect of oxytocin on the human corpus luteum. In view of the inhibitory action of oxytocin, increased se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

1984
1984
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 9 publications
2
24
2
Order By: Relevance
“…As shown in Table 1, the length of the menstrual cycle, luteal phase, and the time from the initiation of (Fields etal, 1983), ovine , human (Wathes etal, 1982;Khan-Dawood & Dawood, 1983) and monkey (Khan-Dawood et al, 1984) luteal tissue, and oxytocin inhibits progesterone synthesis by human luteal cells in vitro (Tan et al, 1982), we suggest that oxytocin may play a role in the primate luteolytic process. Alternatively, oxytocin may be non-specifically toxic or unphysiologically disruptive.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…As shown in Table 1, the length of the menstrual cycle, luteal phase, and the time from the initiation of (Fields etal, 1983), ovine , human (Wathes etal, 1982;Khan-Dawood & Dawood, 1983) and monkey (Khan-Dawood et al, 1984) luteal tissue, and oxytocin inhibits progesterone synthesis by human luteal cells in vitro (Tan et al, 1982), we suggest that oxytocin may play a role in the primate luteolytic process. Alternatively, oxytocin may be non-specifically toxic or unphysiologically disruptive.…”
Section: Resultsmentioning
confidence: 62%
“…The infusion rate of oxytocin (10 mi.u./pl/h) was chosen to approximate physiological rather than pharmacological concentration and is based on our current knowledge of the oxytocin content in human Khan-Dawood & Dawood, 1983) and monkey (Khan-Dawood et al, 1984) luteal tissue. It was 40-80-fold lower than the dose used during in-vitro investigations (Tan et al, 1982). However, the actual content of oxytocin in the corpus luteum has not been determined, and therefore the possibility remains that the dose is above the physiological production rate.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…There must be some sort of communication between the cell types. One possible candidate for mediating this communication is oxytocin, since: (1) oxytocin has been shown to be present in large luteal cells (Rodgers, O'Shea, Findlay, Flint & Sheldrick, 1983b;Guldenaar, Wathes & Pickering, 1984;Sawyer & Moeller, 1985); (2) cloprostenol, an analogue of PGF-2a, has been shown to stimulate the release of oxytocin by the corpus luteum (Flint & Sheldrick, 1982); and (3) oxytocin has been reported to inhibit the ability of hCG to stimulate progesterone secretion by bovine (Tan, Tweedale & Biggs, 1982a) and human (Tan et al, 1982b) luteal tissue. However, some investigators have found no effect of oxytocin on progesterone secretion by human luteal tissue (Richardson & Masson, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with our earlier study on oxytocin receptors in sheep (Sernia et ai, 1989). However, there are reports in pigs (Einspanier et al, 1986;Przala et ai, 1986a, b;Pitzel et al, 1988Pitzel et al, , 1990, cattle (Schams, 1987(Schams, , 1989 and women (Tan et al, 1982b;Bennegard et ai, 1987) which, while supporting an inhibitory role, shows oxytocin effects in the nonpregnant condition. These obser¬ vations need to be reconciled with the comparable studies by Richardson & Masson (1985), Duncan et ai (1961) and Gilbert et al (1989), which show no oxytocin effect on progesterone secretion.…”
Section: Discussionmentioning
confidence: 97%